Charlesworth & Morse company law - Charlesworth, J. [ (John)] , 1893-1957; Charlesworth, J. [ (John)] , 1893-1957; Morse, Geoffrey (Sweet & Maxwell, 1999)
Provides explanations of all aspects of company law. The writing style of this text is succinct and aims to be easy to read